Public relations' robot: utopia or reality? - Dendi Pratama; Mateo Jose A. Vidal; Dade Prat Untarti; Dian Wardiana Sjuchro; Rahmatiah (Faculty of Communications Science, Dr. Soetomo University, 2023)
In 2023, AI has become an integral part of daily life, swiftly embraced in both developed and smaller countries. This research focuses on raises the question: is AI a utopia or an inevitability, given the disruptions it brings to the digital landscape? Using Roger Fidler's mediamorphosis analysis, this research suggests that AI leans more towards a utopian outlook, where its disruptive impact allows for critical evaluation. The study aims to understand AI's value and conceptualisation in society. By recognising AI's transformative influence, this research contributes to the discourse by highlighting its potential as a utopian force while acknowledging its inevitable role in shaping the future.